2014
DOI: 10.1371/journal.pone.0113864
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of the Impact of Different Substrates on Metabolite Production, Energy Extraction and Composition of Gut Microbiota from Lean and Obese Subjects

Abstract: The aim of this study was to investigate the effect of galacto-oligosaccharides, lactulose, apple fiber and sugar beet pectin on the composition and activity of human colonic microbiota of lean and obese healthy subjects using an in vitro model of the proximal colon: TIM-2. Substrate fermentation was assessed by measuring the production of short-chain and branched-chain fatty acids, lactate and ammonia and by studying the composition of the bacterial communities over time. The results suggest that energy harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 68 publications
3
58
0
Order By: Relevance
“…It showed that substrate type determined which of the two microbial compositions had the highest fermenting capacity. Whereas the obesity-associated microbiota produced more SCFAs in response to galacto-oligosaccharides and lactulose, the opposite was true for pectin and fibers [28].…”
Section: Diet and The Microbiotamentioning
confidence: 90%
“…It showed that substrate type determined which of the two microbial compositions had the highest fermenting capacity. Whereas the obesity-associated microbiota produced more SCFAs in response to galacto-oligosaccharides and lactulose, the opposite was true for pectin and fibers [28].…”
Section: Diet and The Microbiotamentioning
confidence: 90%
“…The fecal samples were diluted with protectant-containing solution 1:4 as described in Adamberg et al [23] and kept at −80°C until use. Before cultivation experiment, the fecal slurries were thawed, and pooled in equal volumes as also reported earlier by Aguirre et al [24] The OW pool for inoculation consisted of seven fecal slurries of the OW children (4 boys, 3 girls) and the NW pool consisted of six fecal slurries of the NW children (2 boys, 4 girls). The average age and range of the fecal donors were 10.6 ± 2.4 (range 7–14 years) and 9.4 ± 4.7 (range 4.5–15 years) for OW and NW fecal pools, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, increasing evidence suggests that the gut microbiota plays an important role in human obesity (Harris et al 2012;Aguirre et al 2014;Guida and Venema 2015). Several important discoveries have been made from which we highlight: (i) the impact of dietary components on the composition of gut microbiota.…”
Section: Introductionmentioning
confidence: 94%
“…Nearly 1.5 kg of bacteria reside in the human gut (Nicholson et al 2005), and approximately 50 % of the wet weight of fecal biomass in humans is estimated to come from bacterial cells (Zhao 2013). The identification and analysis of the metabolic capacity and phylogeny from these gut microbial communities unfold specific characteristics in healthy and unhealthy subjects (Ramakrishna 2013;Aguirre et al 2014). Therefore, it has been possible to propose a potential causative role for the microbiota in several types of disorders (Faith et al 2014).…”
Section: Introductionmentioning
confidence: 99%